The Comparison Level of Parent’s Knowledge towards Interdigital Tinea Pedis (Athlete’s foot) in Parents with and without Interdigital Tinea Pedis in Namu Trasi - Meirin Yustisya (Sumatera Medical Journal, 2022)
Background: Tinea pedis occurs in 30-70% of the world's population. In Indonesia, some data are known, such as statistical data on the prevalence of tinea pedis in several teaching hospitals, such as RS. Dr. Soetomo, RSCM, RS. Dr. Hasan Sadikin, RS. Dr. Sardjito obtained a relative yield of 16%. Therefore, public knowledge about tinea pedis is something that is very relatively owned by the community to respond to, control, and prevents the occurrence of tinea pedis. Objective: The purpose of this study was to compare the level of parental knowledge of Interdigital Tinea Pedis (Athlete’s foot) in parents with and without Interdigital Tinea pedis in Namu Trasi. Method: This research was conducted using an analytical method of cross-sectional design with a collection technique using a questionnaire to be filled out by the respondent and then analyzed using a statistical program application. Results: The level of knowledge of parents with and without Interdigital Tinea pedis in Namu Trasi Village was 45.8% with good knowledge, 34.7% with sufficient knowledge, and 19.4% with poor knowledge. Conclusion: There is a significant difference between the level of parental knowledge of Interdigital Tinea pedis (Athlete’s foot) in patients and non-patients with Interdigital Tinea pedis in Namu Trasi